Species diversity and traditional utilization of bamboos (Poaceae) on the Phu Thai Ethnic Group in northeastern Thailand - SUMRUAY SUDCHALEAW; SURAPON SAENSOUK; PIYAPORN SAENSOUK; SARAWOOD SUNGKAEW (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Sudchaleaw S, Saensouk S, Saensouk P, Sungkaew S. 2023. Species diversity and traditional utilization of bamboos (Poaceae) on the Phu Thai Ethnic Group in northeastern Thailand. Biodiversitas 24: 2261-2271. The study of species diversity by survey method and traditional utilization by interviewing local philosophers, folk healers, elders, and villagers with semi-structured interviews of bamboos (Poaceae) in the Phu Thai Ethnic Group in four provinces including Kalasin, Mukdahan, Nakhon Phanom, and Sakon Nakhon Provinces, in the Northeast of Thailand was conducted from May 2019 to August 2021. In addition, the aim of this research is to study the species diversity and traditional utilization of Bamboo (Poaceae) in the Phu Thai Ethnic Group in Nakhon Phanom, Sakon Nakhon, Kalasin, and Mukdahan Provinces, in Northeastern Thailand. Survey Five genera, and 13 species including Bambusa bambos (L.) Voss, B. beecheyana Munro, B. burmanica Gamble, B. nutans Wall. ex Munro, B. spinosa Roxb., B. vulgaris Schrad. ex J.C.Wendl., Dendrocalamus asper (Schult. & Schult.f.) Backer ex K. Heyne, D. giganteus Munro, D. sinicus L.C. Chia & J.L.Sun, Gigantochloa albociliata (Munro) Kurz, Thyrsostachys siamensis Gamble, ×Thyrsocalamus liang Sungkaew & W.L. Goh, and Vietnamosasa pusilla (A. Chev. & A. Camus) T.Q. Nguyen were found. The genus with the highest species is Bambusa, with seven species, followed by Dendrocalamus (3 species). One species per genus was found in the other three genera: Gigantochloa, Thyrsostachys, and Vietnamosasa. Vernacular name, distribution, ecology, and phenology are present here. The traditional utilization of bamboos in the Phu Thai Ethnic Group in these four provinces indicated that bamboo was used as food for 13 species from five genera. While six species in three genera were used for medicinal purposes, 13 species from five genera were used as equipment, appliances, and housing materials, seven species from four genera were used as ornamental plants, and 13 species from five genera were used in ritualistic ceremonies. The data on species diversity and traditional utilization of bamboos in the Phu Thai Ethnic Group in these four provinces in Northeastern Thailand were newly reported.